Assessing the impact of a wage subsidy for single parents on social assistance in Canada - Guy Lacroix (Institute for the Study of Labor (IZA), 2009)
In 2002 the Quebec government implemented the Action Emploi (AE) program aimed at making work pay for long-term social assistance recipients (SA). AE offered a generous wage subsidy that could last up to three years to recipients who found a full-time job within twelve months. The program was implemented on an experimental basis for a single year. Based on little empirical evidence, a slightly modified version of the program was implemented on permanent basis in May 2008. The paper investigates the impact of the temporary program by focusing on the labour market transitions of the targeted population starting one year before the implementation of the program and up until the end of 2005. We use a multi-state multi-episode model. The endogeneity of the participation status is accounted for by treating AE as a distinct state and by allowing correlated unobserved factors to affect the transitions. The model is estimated by the method of simulated moments. Our results show that AE has indeed increased the duration of Off-SA spells and decreased the duration of SA spells slightly. There is also some evidence that the response to the program varies considerably with unobserved individual characteristics.
urn:nbn:de:101:1-20090513323
Keywords: I38; J31; J64; 330; Wage subsidy; multi-state multi-episode transition model; social assistance; Lohnsubvention; Sozialhilfeempfänger; Alleinerziehende; Wirkungsanalyse; Berufliche Integration; Kanada